2014
DOI: 10.1002/pc.23038
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, morphology, and thermal properties of carbon fiber reinforced poly(butylene succinate) composites

Abstract: Biodegradable poly(butylene succinate) (PBS)/carbon fiber (CF) composites were prepared by melt blending method using twin-screw extruder followed by injection molding. Mechanical properties, crystallization behavior, morphology, crystal structure, and thermal stability of PBS/CF composites were investigated with different CF contents (0, 5, 10, 15, and 20 wt%). It was found that the tensile and impact properties of the composites were improved markedly with the addition of CF; while too much CF would lead to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 44 publications
4
19
0
Order By: Relevance
“…A well dispersed nanosheet would form an effective barrier to volatile molecules produced during the PBS thermal decomposition. A similar result was obtained for other filler reinforced PBS nanocomposites .…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…A well dispersed nanosheet would form an effective barrier to volatile molecules produced during the PBS thermal decomposition. A similar result was obtained for other filler reinforced PBS nanocomposites .…”
Section: Resultssupporting
confidence: 88%
“…In the case of nanocomposites, the diffraction peaks more or less were unchanged from neat PBS indicating that the incorporation of graphene nanosheets in the PBS matrix did not alter the crystal forms. A similar observation was made by Liang et al in carbon fiber reinforced PBS composites . Additional insights into the crystal forms gained from the FTIR‐ATR spectra of pure PBS and its nanocomposites are presented in Fig.…”
Section: Resultssupporting
confidence: 81%
“…This could be due to a deterioration in the mobility of the chains as the SA content increased, which led to a significant reduction in the flexibility of PBS [36]. The fragility of copolymers was due to the rigidity of its benzene ring, which increased the copolymer's steric hindrance as SA content increased [37].…”
Section: Resultsmentioning
confidence: 99%
“…Polymer composite containing carbon fiber is wildly used in industry due to excellent thermal, electrical and mechanical properties they can be used as a flexible electric sensor according to high sensitivity to strain and low industrial costs [1][2][3]. Many researchers indicated that the electrical conductivity of the polymer/carbon-fibre composite could be influenced by its deformation [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%